Inovasi Kecerdasan Komputer Mendorong Masa Depan Bioinformatika yang Lebih Cerdas (Jurnal Sistem Informasi dan Ilmu Komputer, 2025)
Computer intelligence, particularly Artificial Intelligence (AI), has become a cornerstone in advancing bioinformatics. This study aims to explore the role of AI in addressing the challenges of analyzing complex biological data, especially in genomics, proteomics, and metabolomics. Using machine learning (ML) and deep learning (DL) algorithms, AI efficiently processes large-scale data, accelerates genomic research, predicts protein structures, and identifies disease biomarkers. However, challenges such as data quality, computational limitations, and privacy issues remain barriers to its implementation. The findings of this study highlight the importance of continuous innovation, multidisciplinary collaboration, and strict regulations in AI applications. In conclusion, AI holds great potential to revolutionize bioinformatics, significantly impacting scientific research and the development of global healthcare systems.